SuperKEKB positron beam tuning using machine learning - Natsui Takuya (EPJ Web of Conferences)
In the KEK injector linac, four-ring simultaneous top-up injection has been achieved, and beam tuning is always performed in various beam modes. As there are four beam modes, the optimum magnet current and RF phase must be selected for each. There are numerous tuning knobs for each mode; thus, it takes signiﬁcant time and manpower to ﬁnd the optimum state for all modes. In particular, tuning the positron primary electron beam requires delicate parameter adjustment due to its large charge. Signiﬁcant time has been spent on this tuning. Therefore, an automatic tuning tool has been developed. Automatic tuning is realized using Bayesian optimization and the downhill simplex method. This tool can be used for any beam tuning on our system and has been particularly useful for positron beam tuning.